2021
DOI: 10.3390/su13084475
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Management Strategies of the Terraced Agricultural Systems and Conservation Actions to Maintain Cultural Landscapes around the Mediterranean Area

Abstract: Coupled human–environment systems and traditional agricultural landscapes can be a key element in the conservation of biodiversity, ecological functionality, and cultural heritage. Terraced landscapes are a relevant example of traditional landscapes within the Mediterranean area, but they are now threatened due to the abandonment of agricultural activities. In order to identify factors that can affect the conservation strategies needed to maintain terraced landscapes in the Mediterranean area, we performed a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 75 publications
(104 reference statements)
0
6
0
Order By: Relevance
“…To evaluate winegrowers' perceptions, an online questionnaire was administered to winegrowers operating in the case study area. This particular type of stakeholder was chosen according to Cicinelli et al [39], who highlighted the strategic role of local farmers in maintaining terraced landscapes. The use of a questionnaire administered via the Internet is well established in the literature [58].…”
Section: Evaluation Of Winegrowers' Perceptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate winegrowers' perceptions, an online questionnaire was administered to winegrowers operating in the case study area. This particular type of stakeholder was chosen according to Cicinelli et al [39], who highlighted the strategic role of local farmers in maintaining terraced landscapes. The use of a questionnaire administered via the Internet is well established in the literature [58].…”
Section: Evaluation Of Winegrowers' Perceptionsmentioning
confidence: 99%
“…Furthermore, the importance of different stakeholders' involvement in the assessment, management, and policy planning of terraced landscapes has been recognized by many authors [36][37][38]. However, recent research showed a lack of studies on local farmers' involvement in decision making regarding the conservation of terraced landscapes [39]. The close link that has always existed, specifically between terraced vineyard landscapes and winegrowers, using an approach from expert-based assessment of historical landscape elements and dynamics to perceptive studies, is unexplored.…”
Section: Introduction 1terraced Landscapes and Rural Communitiesmentioning
confidence: 99%
“…Mountain farmers are often motivated by social and cultural factors. Although these incentives do not generate income directly, they contribute to the maintenance of mountain landscapes, which provide indispensable ecosystem services, sustain the natural production base, and support development beyond rural mountain areas (Bernues et al 2014;Schirpke et al 2016;Cicinelli et al 2021). Mountain farmers are also custodians of place identity, cultural values, and indigenous knowledge, which is exemplified by the terraced landscapes found in all major mountain regions of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Two main types of terraces are used in the Mediterranean region, namely earth embankments and dry stone terraces, with possible use of mixed types (Cicinelli et al, 2021). Lebanon features dry stone walls as vertical elements to create horizontal strips of land cultivated with tree crops, such as mulberry (historically used for silk production), vines, olives, figs, walnut and, most recently, apple and cherries (Zurayk, 1994).…”
Section: Introductionmentioning
confidence: 99%